Perhitungan Rugi Daya Saluran Distribusi Primer 20 kV Feeder Adi Sucipto di GI Garuda Sakti Dengan Metode Ladder Iterative Technique - Ardi Syaputra; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The Imbalance loads of distribution channel in a power system always happened, and the imbalance caused by the presence of conductive permanent resistance. Good conductor should not have resistance, but in reality every object has a resistance to electricity. Therefore it is necessary for the calculation of the power losses generated by the conductor. In this research power loss calculations made on the primary distribution system, namely when the system load. Total power loss that has generated in this study are at 791,995.227 Watt and the percentage of power loss to the average load is equal to 10.345%.Keywords : Loss of power, The Imbalance Load, the primary distribution system